2017
DOI: 10.1002/2017jb014111
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 3‐D fracture setting of an unstable rock mass: From surface and seismic investigations to numerical modeling

Abstract: The characterization of the fracturing state of a potentially unstable rock cliff is a crucial requirement for stability assessments and mitigation purposes. Classical measurements of fracture location and orientation can however be limited by inaccessible rock exposures. The steep topography and high‐rise morphology of these cliffs, together with the widespread presence of fractures, can additionally condition the success of geophysical prospecting on these sites. In order to mitigate these limitations, an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
1
25
0
4
Order By: Relevance
“…No significant changes in the parameters are observed between events occurring in dry or wet conditions. Conversely, a strong air temperature control on the peak frequencies in the Fourier spectra of the recorded events (Figure g) is identified, as already highlighted for ambient noise resonance frequencies in Colombero et al (). Air temperature and frequency fluctuations are almost in phase, with maximum frequency during the hottest hours and lower values in cold periods.…”
Section: Microseismicity At the Field Scalesupporting
confidence: 63%
See 1 more Smart Citation
“…No significant changes in the parameters are observed between events occurring in dry or wet conditions. Conversely, a strong air temperature control on the peak frequencies in the Fourier spectra of the recorded events (Figure g) is identified, as already highlighted for ambient noise resonance frequencies in Colombero et al (). Air temperature and frequency fluctuations are almost in phase, with maximum frequency during the hottest hours and lower values in cold periods.…”
Section: Microseismicity At the Field Scalesupporting
confidence: 63%
“…Past displacement monitoring measurements at the site (Regione, ) highlighted similar reversible modifications in fracture openings due to the seasonal thermal dilation of the rock mass. Colombero et al () detected coherent temperature‐driven seasonal reversible variations in the resonance frequencies of the unstable blocks from ambient seismic noise recordings. The detected MS activity seems therefore emphasized during the periods of rock mass thermal expansion.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, fracture K4 shows an evident displacement step on the panoramic square located at the top of the cliff. The investigation found that the fracture is open up to a depth of about 16 m [21].…”
Section: Structural and Geomechanical Characterizationmentioning
confidence: 94%
“…Lancellotta et al [18,22] made a geomechanical characterization of the site. The detailed investigation carried out also using geophysical methods by Colombero et al [20,21,27] allowed a good improvement of the knowledge of this case. In particular, Colombero et al [21] identified an open and pervasive fractures system delimiting two prone-to-fall sectors (A and B) having estimated volumes of 6000 and 6300 m 3 , respectively ( Figure 3).…”
Section: Structural and Geomechanical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation